Molecular screening program to select molecular-based recommended therapies for metastatic cancer patients: analysis from the ProfiLER trial. (13th March 2019) - Trédan, O; Wang, Q; Pissaloux, D; Cassier, P; de la Fouchardière, A; Fayette, J; Desseigne, F; Ray-Coquard, I; de la Fouchardière, C; Frappaz, D; Heudel, P -E; Bonneville-Levard, A; et al.
Abstract: Background: Antitumor activity of molecular-targeted agents is guided by the presence of documented genomic alteration in specific histological subtypes. We aim to explore the feasibility, efficacy and therapeutic impact of molecular profiling in routine setting. Patients and methods: This multicentric prospective study enrolled adult or pediatric patients with solid or hematological advanced cancer previously treated in advanced/metastatic setting and noneligible to curative treatment. Each molecular profile was established on tumor, relapse or biopsies, and reviewed by a molecular tumor board (MTB) to identify molecular-based recommended therapies (MBRT). The main outcome was to assess the incidence rate of genomic mutations in routine setting, across specific histological types. Secondary objectives included a description of patients with actionable alterations and for whom MBRT was initiated, and overall response rate. Results: Four centers included 2579 patients from February 2013 to February 2017, and the MTB reviewed the molecular profiles achieved for 1980 (76.8%) patients. The most frequently altered genes were CDKN2A ( N = 181, 7%), KRAS ( N = 177, 7%), PIK3CA ( N = 185, 7%), and CCND1 ( N = 104, 4%). An MBRT was recommended for 699/2579 patients (27%), and only 163/2579 patients (6%) received at least one MBRT. Out of the 182 lines of MBRT initiated, 23 (13%) partial responses were observed. However, only 0.9% of the whole cohort experienced an objective response. Conclusion: An MBRT was provided for 27% of patients in our study, but only 6% of patients actually received matched therapy with an overall response rate of 0.9%. Molecular screening should not be used at present to guide decision-making in routine clinical practice outside of clinical trials. This trial is registered with ClinicalTrials.gov, number NCT01774409.